Criminal Offense of Adultery in Indonesia from the Perspective of Legal Sociology - Romli, Hawina; Subekti, Rahayu (International Journal of Sustainability in Research, 2024)
The values underlying the understanding of the crime of adultery in the Criminal Code are still strongly influenced by Western values. The law that applies in society must take into account the values that are prevalent in the community where the law develops. Legal policy is an integral part of social policy, where the main objective is the safety and well-being of the community. Therefore, legal policies regarding the crime of adultery must also take into account the values, culture, and social structure that have already been established. The formulation of the crime of adultery and its renewal must be verified through sociological approaches. This type of research is normative with the characteristics of prescriptive research, and the analysis technique used is the deductive method. The crime of adultery has been revised in the new Criminal Code, which includes an expansion of the material that differs from the old Criminal Code. That the offense of adultery in the latest Criminal Code already meets and reflects the values, norms, morals, and religion of Indonesian society.